Upacara Gaukang Tu Bajeng Kabupaten Gowa 1945-2017 - Kusuma Ningrum; Najamuddin Najamuddin; Asmunandar Asmunanda (PATTINGALLOANG, 2017)
This study aims to know the background behind the formation of  Gaukang in South Sulawesi society, Gaukang Tu Bajeng Ceremony in the early days of independence and now, and the public view of Gaukang Tu Bajeng ceremony of Gowa district. This study is historical descriptive by using historical research methods, through the stages of work that includes; heuristics, criticism, interpretation, and historiography. Heuristics is the stage of collecting historical sources, the source is then criticized for getting the facts with other facts. As the last stage is historiography or presentation, which is reconstructing historical events into historical stories in the form of historical descriptive. The results showed that Gaukang as a symbol of the strength of ancestors believed by the public as a talisman that can save them. Gaukang become a sacred and highly respected object. The interest of Mr. Fukusima to see Gaukang objects in Bajeng / Limbung make Limbung society hold a ceremony called Ceremony Gaukang tu Bajeng. This ceremony is held every year to commemorate the heroes of the Limbung / Bajeng region in seizing and maintaining independence.